Representation of Environmental Damage in Tere Liye's Novel Rain (Literary Ecocriticism Study) - Arisa Arisa; Nur Rahmi (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2024)
The sophistication of technology helps modern man in the pace of activity and creativity. However, sophisticated technology without control from humans as its creators can bring disaster and prolonged damage that has a global impact. This study aims to describe the representation of environmental damage in the novel Rain by Tere Liye. The type of research used is qualitative descriptive with Greg Garrard's literary ecocriticism approach. The research data was sourced from the novel Hujan by Tere Liye published by Gramedia Pustaka Utama with research data in the form of words, phrases, sentences related to environmental damage. Data collection techniques in this study are carried out by document techniques and literature studies, data analysis through the stages of data reduction, data presentation, and drawing conclusions. The results of the study illustrate that in the novel Rain by Tere Liye there is environmental damage which includes pollution, wilderness, disasters, housing / shelter, animals, and the earth. Environmental damage occurs due to the utilization of sophisticated technology without control from humans, used as a savior with fast-paced action, but only helps in the short term. The conclusions of the research represent environmental damage in the novel Rain by Tere Liye due to sophisticated technology and low human empathy for the environment as a result of modernism.